The Role of Crop Production Practices and Weather Conditions in Microbiological Safety of Tomatoes and Peppers - Massimiliano Marvasi; George Hochmuth; Max Teplitski (EDIS)
Salmonella and other human pathogens can contaminate produce at any stage from “farm to fork.” If we can better understand how production practices may make crops more or less susceptible to human pathogens, we may be able to significantly reduce the number and severity of the produce-associated outbreaks. This 3-page fact sheet provides up-to-date information about tomato production practices and their relationships with Salmonella. Written by Massimiliano Marvasi, George Hochmuth, and Max Teplitski, and published by the UF Department of Soil and Water Science, December 2014. (Photo: Max Teplitski, UF/IFAS)